Pengembangan Media Video Pembelajaran Matematika dengan Model Assure - Budi Purwanti (Universitas Muhammadiyah Malang, 2015)
Pengembangan Media Video Pembelajaran Matematikadengan Model AssureBudi PurwantiGuru SMK Negeri 2 Kota ProbolinggoEmail: budipurwanti47@gmail.comAbstract:The development of this research was to streamline learning and change students’ perception towards mathematics learning to the materials of measure of statistical data presentation of 12th grade in even semester. The development of research was conducted in order to solve the problem faced by students who find the difficulty as many formulas in mathematics lesson. The research was conducted by Research and Development. The making process of learning video media consists of three processes, namely preparation, production stage and post-production. After the media were produced, then, the media were tested to the experts of materials, the experts of learning design, the experts of learning media and its storyboard. Then, they were tested towards small groups and large groups to know the attractiveness so that it can be concluded that the video media development of mathematics learning of basic competence of the measure of statistical data presentation with ASSURE model can be used as learning mediaKeywords: development, video media of learning, assure modelAbstrak:Pengembangan penelitian ini untuk mengefektifkan pembelajaran dan mengubah presepsi peserta didik terhadap pembelajaran matematika pada materi ukuran penyajian data statistik kelas XII semester Genap. Pengembangan penelitian dilakukan supaya dapat mengatasi permasalahan yang dihadapi peserta didik yang merasa kesulitan mengingat begitu banyak rumus dalam pelajaran matematika. Penelitian dilakukan dengan Research and Development. Poses pembuatan media video pembelajaran terdapat tiga proses yaitu, proses persiapan, tahap produksi dan pasca produksi. Setelah media diproduksi kemudian media diujicobakan pada ahli materi, ahli desain pembelajaran, ahli media pembelajaran dan story boardnya, kemudian diujicobakan terhadap kelompok kecil dan kelompok besar, untuk mengetahui daya tarik sehingga dapat diambil simpulan bahwa pengembangan media video pembelajaran matematika kompetensi dasar ukuran penyajian data statistik dengan model ASSURE dapat digunakan sebagai media pembelajaran.Kata kunci: pengembangan, media video pembelajaran, model assure,